Differences in biomarker concentrations and prediction of long-term outcome in patients with ST-elevation and non-ST-elevation myocardial infarction. (14th October 2021) - Hjort, M; Eggers, K M; Lindhagen, L; Baron, T; Erlinge, D; Jernberg, T; Marko-Varga, G; Rezeli, M; Spaak, J; Lindahl, B
Abstract: Background: Biomarkers offer insights into the pathobiology of myocardial infarction (MI). Differences in biomarker concentrations and its prognostic implications in ST-elevation MI (STEMI) and non-STEMI (NSTEMI) are incompletely understood and may offer insights into tailored treatment. Purpose: We aimed to characterise differences in activation of pathophysiologic pathways in patients with acute STEMI versus NSTEMI by comparing multiple biomarkers, and investigating their prognostic implications. Methods: 538 STEMI and 544 NSTEMI patients were included in our hospitals between 2008–2014. Blood samples were collected shortly after admission and 92 biomarkers were analysed using Proximity Extension Assay and 87 biomarkers using Multiple Reaction Monitoring mass spectrometry. Adjusted Lasso analysis (penalized logistic regression) was used to select biomarkers that discriminated STEMI from NSTEMI patients. For biomarkers that were identified by the Lasso analysis, concentrations (log2-transformed) were then evaluated in adjusted Cox regressions on associations with death or major cardiovascular events (MACE), a composite of death, hospitalization for MI, ischemic stroke or heart failure. Results: Eleven biomarkers differed between STEMI and NSTEMI patients (Table) with higher OR (>1.00–1.42) and concentrations in STEMI patients of myoglobin, N-terminal pro-B-type natriuretic peptide (NT-proBNP), serum amyloid A-1 (SAA1) and serum amyloid A-2 (SAA2) protein, ST2 protein, interleukin-6 (IL-6) and chitinase-3-like protein 1 (CHI3L1). NSTEMI patients had lower OR (0.83-<1.00) and higher concentrations of fibroblast growth factor 23 (FGF 23), membrane-bound aminopeptidase P (MAMP), tumour necrosis factor-related activation-induced cytokine (TRANCE) and apolipoprotein C-I. During up to 6.6 years of prognostic follow-up, all of the biomarkers except MAMP displayed significant prognostic information in STEMI and/or NSTEMI patients. However, interaction analyses indicated that all biomarkers were similarly predictive (p>0.05) of death or MACE between MI groups. Conclusions: In the acute setting, biomarkers indicated greater myocardial dysfunction and inflammation in STEMI patients, whereas NSTEMI patients displayed a heterogeneous and more ambiguous activation of pathophysiologic pathways. These biomarkers were not associated with prognostic differences between STEMI and NSTEMI patients. Therefore, the results do not support treating STEMI and NSTEMI patients differently based on these biomarkers. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swedish Foundation for Strategic Research. Swedish Association of Local Authorities and Regions.